Combinatory Exposure to Urolithin A, Alternariol, and Deoxynivalenol Affects Colon Cancer Metabolism and Epithelial Barrier Integrity in vitro - Groestlinger, Julia; Seidl, Carina; Varga, Elisabeth; Del Favero, Giorgia; Marko, Doris (Frontiers in Nutrition, 2022)
The human gastrointestinal tract (GIT) is the primary site of nutrient absorption, as well as a crucial barrier against xenobiotics. It regularly faces “chemical cocktails” composed of food constituents, human and microbial metabolites, and food borne contaminants, such as mycotoxins. Hence, the colonic epithelium adapts to dietary molecules tuning its immune response, structural integrity, and metabolism to maintain intestinal homeostasis. While gut microbiota metabolites of berry ellagitannins, such as urolithin A (Uro A) might contribute to a physiological epithelial barrier integrity, food-borne co-contaminating mycotoxins like alternariol (AOH) and deoxynivalenol (DON) could hamper epithelial function. Hence, we investigated the response of differentiated Caco-2 cells (clone C2BBe1) in vitro to the three compounds alone or in binary mixtures. In virtue of the known interactions of Uro A, AOH and DON with the aryl hydrocarbon receptor (AhR) pathway, potential effects on phase-I-metabolism enzymes and epithelial structural integrity were taken as endpoints for the evaluation. Finally, LC-MS/MS measurements elucidated the cells’ absorption, secretion, and metabolic capacity under single and combinatory exposures. Uro A and AOH as single compounds, and as binary mixture, were capable to induce CYP 1A1/1A2/1B1 enzymes triggered by the AhR pathway. In light of its ribosome inhibiting capacity, the trichothecene suppressed the effects of both dibenzo-α-pyrones. In turn, cellular responsiveness to Uro A and AOH could be sustained when co-exposed to DON-3-sulfate, instead of DON. Colonic epithelial structural integrity was rather maintained after incubation with Uro A and AOH: this was reinforced in the combinatory exposure scenario and disrupted by DON, an effect, opposed in combination. Passage through the cells as well as metabolism of Uro A and AOH were rather influenced by co-exposure to DON than interacting with each other. Therefore, we conclude, although single food borne bioactive substances individually could either support or disrupt colon cancer epithelial structure and metabolic capacity, exposure to chemical mixtures changes the experimental outcome and calls for the need of combinatory investigations for proper risk assessment.